2020
DOI: 10.1038/s41467-020-15062-w
|View full text |Cite
|
Sign up to set email alerts
|

Deep high-temperature hydrothermal circulation in a detachment faulting system on the ultra-slow spreading ridge

Abstract: Coupled magmatic and tectonic activity plays an important role in high-temperature hydrothermal circulation at mid-ocean ridges. The circulation patterns for such systems have been elucidated by microearthquakes and geochemical data over a broad spectrum of spreading rates, but such data have not been generally available for ultra-slow spreading ridges. Here we report new geophysical and fluid geochemical data for high-temperature active hydrothermal venting at Dragon Horn area (49.7°E) on the Southwest Indian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(148 citation statements)
references
References 66 publications
8
135
1
1
Order By: Relevance
“…Correspondence to: L. Chang, and C. Tao,liao.chang@pku.edu.cn;taochunhuimail@163.com Citation: Wang, S., Chang, L., Wu, T., & Tao, C. (2020). Progressive dissolution of titanomagnetite in high-temperature hydrothermal vents dramatically reduces magnetization of Basaltic Ocean crust.…”
Section: /2020gl087578mentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondence to: L. Chang, and C. Tao,liao.chang@pku.edu.cn;taochunhuimail@163.com Citation: Wang, S., Chang, L., Wu, T., & Tao, C. (2020). Progressive dissolution of titanomagnetite in high-temperature hydrothermal vents dramatically reduces magnetization of Basaltic Ocean crust.…”
Section: /2020gl087578mentioning
confidence: 99%
“…It has been found that most hydrothermal vents along slow-spreading Atlantic are hosted on detachment faults, whose interfaces and related fissures provide important fluid paths for hydrothermal circulation (deMartin et al, 2007;Humphris et al, 2015;McCaig et al, 2007). The same scenario may exist at SWIR, and there is evidence for multistage detachment faulting at the Longqi site (Tao et al, 2020). As up-flow fluids penetrate the fissures in the hanging wall, heat and fluid pressure further hydrofracture country rocks, producing hydrothermal breccias.…”
Section: Geophysical Research Lettersmentioning
confidence: 99%
“…Previous reports showed that the concentrations of reduced components (i.e., CH 4 , sulphur substances, and hydrogen) in the endmember fluid from the Longqi field are comparable or higher than those in the vents along the Central Indian Ridge 25,26,27 . Although methane is enriched in Longqi compared to other vents on the Central Indian Ridge 26 , further biogenic methane input from microbes living below and around the community may be sufficient to sustain the MOB.…”
Section: Energy Resourcesmentioning
confidence: 92%
“…At slow spreading ridges, fluid circulation may extend much deeper (up to 35 km) into the ultramafic mantle (Schlindwein and Schmid, 2016), although the maximum extent of the brittle layer remains debated and may be confined to the upper 15 km (Grevemeyer et al, 2019). Such deep-reaching fluid flow can sometimes be channelized along deep detachments at fault-controlled systems such as TAG and Lonqi (Tao et al, 2020;deMartin et al, 2007) and/or may propagate to greater depths via thermal cracking (Olive and Crone, 2018;Lister, 1974). Temperatures can also vary over large ranges with high-temperature systems typically being driven by a magmatic heat source of 1000 • C or more and 1 https://doi.org/10.5194/gmd-2020-140 Preprint.…”
Section: Introductionmentioning
confidence: 99%
“…to solve a wide range of problems. Examples include Schultz (2000, 2004), who showed that hydrothermal systems operate close to optimal efficiency with their maximum vent temperatures set by the thermodynamic properties of water, studies that revealed the complex 3-D structure of recharge and discharge flow in mid-ocean ridge hydrothermal systems (Hasenclever et al, 2014;Coumou et al, 2008;Fontaine et al, 2014), dedicated case studies for individual vent systems (Tao et al, 2020;Andersen et al, 2015;Lowell et al, 2012), and models exploring tidal forcing of hydrothermal circulation (Crone and Wilcock, 2005; Barreyre et al, 2018). This list is nowhere near complete and there are many more examples.…”
Section: Introductionmentioning
confidence: 99%